EMPOWERING STITM KEDIRI LECTURERS IN WRITING HIGH-QUALITY INTERNATIONAL JOURNAL ARTICLES THROUGH SYSTEMATIC LITERATURE REVIEW (SLR) METHODOLOGY - Benny Prasetiya; Muhammad Alfi Syahrin; Nur Wiji Sholikin (DEVELOPMENT: Journal of Community Engagement, 2025)
The low productivity of international publications among lecturers at small higher education institutions has become a major challenge, affecting both academic reputation and career advancement. Contributing factors include limited understanding of advanced research methodologies such as the Systematic Literature Review (SLR), lack of experience in writing for international journals, and restricted access to academic resources. To address these issues, a community service programme was implemented at STITM Kediri using the Asset-Based Community Development (ABCD) approach to enhance lecturers’ capacity in producing SLR-based international scientific articles. The programme engaged 15 lecturers through four stages: Discovery (mapping academic assets), Dream (formulating a collective vision), Design (developing training plans), and Delivery (implementation and mentoring). The results indicate a substantial improvement in participants’ understanding of the SLR methodology, with the average score rising from 2.1 (on a 1–5 scale) before the training to 4.3 afterwards. All participants were actively engaged (100% attendance, 87% active participation), resulting in 15 article drafts, three of which are ready for submission to reputable international journals (Scopus Q3–Q4). These achievements demonstrate that the ABCD-based training successfully empowered existing academic potential, fostered writing motivation, and strengthened the culture of international publication at STITM Kediri. This model has the potential to be replicated in other small higher education institutions as a strategy for sustainable academic capacity building.